Effect of cybotactic clusters on the elastic and flexoelectric properties of bent-core liquid crystals belonging to the same homologous series - VIJ, JAGDISH; PANOV, VITALI (My University, 2013)
We report results of the splay ( K 11 ) and bend ( K 33 ) elastic constants and the effective flexoelectric coefficient of three bent-core liquid crystals belonging to a homologous series of 4-cyanoresorcinol bisbenzoates with varying chain lengths. Based on the results of x-ray scattering studies, one of the three compounds with a shorter chain length (C4) has few, if any, clusters present in its nematic phase and behaves quite normally, whereas the others two with longer chain lengths (C6 and C7) show the presence of cybotactic nematic phase with smectic C type clusters. These grow in size with a reduction in temperature. K 33 is found to be the least for C7, whereas it is weakly dependent on temperature. K 33 is somewhat higher for C4 and C6 and is almost independent of temperature. K 11 for C6 and C7 is higher by 20% to 50% than C4 depending on the temperature. K 11 increases linearly with a reduction in temperature for the three compounds. For C6 K 11 >K 33 by a factor up to ~ 2 depending on the temperature, for C4 it is greater by a factor up to 1.3, and for C7 it is greater by a factor of ~ 2.5. These results suggest that the clusters do not have any effect on K 11 .
PUBLISHED
Keywords: Physics